Management of Bioculture Potential with Environmental Perspective Based on Local Wisdom - PUTRA, Trio Beni; THAMRIN, Thamrin; SAAM, Zulfan; HUSEIN, Sofyan (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023, 2023)
This paper analyzes how the system for managing bio culture potential is based on the local wisdom of the Duanu tribe, Indragiri Hilir Regency, and aims to develop a strategy for managing potential with an environmental perspective based on the local wisdom of the community. In this regard, is used a mixed method by distributing questionnaires, a sample of 100 respondents using a purposive sampling approach, and data collection techniques using surveys, interviews, and observations. The findings of this study conducted the strategy formulation by determining alternative strategies obtained from the results of the SWOT analysis. The tool used in this analysis is the Quantitative Strategic Planning Matrix to see the priority strategies and set the environmental perspective based on local wisdom.